Glipicam-1 no glioblastoma humano: implicações na tumorigênese e na quimioterapia - Listik, Eduardo [UNIFESP] (2019)
Introduction: Glioblastoma is one of the most common malignant brain tumors, in which patients have a mean survival of 24 months. The scientific literature has revealed evidence that glypican-1 is overexpressed in human glioblastoma and is negatively correlated with patient’s survival. Glypican-1 is a membrane-bound heparan sulfate proteoglycan, and the heparan sulfate GAG chains are classically known to interact with morphogens frequently associated with cancer. Objective: This study aims to investigate how glypican-1 influences the tumoral profile of human glioblastoma using in vitro cell line models. Methods: Glypican-1 was knocked-down from U-251 MG cells using shRNA followed by clonal selection. The glypican-1 silencing effects were assessed by profiling transcriptional discrepancies using RT-qPCR as well as other techniques such as flow cytometry, cell viability, migration, proliferation, adhesion, clonogenicity, and susceptibility to temozolomide. Confocal microscopy was used to investigate glypican1 localization in lipid rafts or its association with syndecan-4 and glypican-3. Results: Glypican-1 was associated with the expression of other heparan sulfate proteoglycans and metalloproteases. By downregulating glypican-1, the cellular growth rate was reduced by up to 71% and proliferation up to 54%, in which cells were significantly shifted towards G0 as opposed to G1 phases. Cellular migration was severely affected and may be almost abolished by negatively modulating glypican-1. Glioblastoma U-251 MG cells poorly adhered to laminin but showed high affinity to type IV collagen and vitronectin. However, glypican-1 solely affected the affinity towards laminin binding of glioblastoma U-251 MG cells, although slower kinetic adhesion profiles were observed when the proteoglycan was knocked down. This proteoglycan was highly prevalent in glioblastoma cells, being primarily localized in the cellular membrane and extracellular vesicles, occasionally with glypican-3. Glypican-1 could also be found in cell-cell junctions with syndecan-4 but was not identified in lipid rafts in this study. Glypican-1 was also revealed to be a probable mediator of temozolomide resistance mechanisms in glioblastoma, as glypican-1-silenced cells were much more susceptible to this alkylating agent than in U-251 MG itself. Conclusion: We present evidence not only to support facts that glypican-1 is an elementary macromolecule in glioblastoma tumoral microenvironment, but also to introduce this proteoglycan as a promising therapeutic target for this highly malignant tumor.